(untitled) (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the 2025 revision of the Indonesian National Armed Forces Law from the perspective of civilian supremacy and the rule of law. The issue is legally important because Law Number 3 of 2025 retains the language of civilian supremacy while at the same time expanding the range of ministries and agencies that may be occupied by active soldiers and revising the retirement-age regime. Using normative legal research with statutory, conceptual, and limited case approaches, this article compares the 2004 and 2025 formulations, identifies the constitutional pressure points they create, and formulates legal parameters to test whether the expansion remains compatible with democratic constitutionalism. The article argues that a revised TNI Law can only remain consistent with civilian supremacy if the expansion of positions is interpreted narrowly, tied directly to defence functions, and placed under strict civilian accountability and exceptional-use standards.